METODE ESTIMASI UMUR UNTUK SPESIFIK POPULASI INDONESIA - Lovina Lovina; Nur Isnaeni; Nurul Wafda Marpunir Rahmah (Yayasan Literasi Sains Indonesia, 2025)
Indonesia has extensive ethnic and biological diversity, which presents unique challenges in the application of age estimation methods, particularly within the context of forensic anthropology. This study aims to review various age estimation methods that have been used in Indonesia over the past ten years, including approaches based on teeth, bones, skulls, and bone histology. Each method is analyzed to the Indonesian population. The findings show that dental methods such as Demirjian, Willems, and the Indonesian Dental Development Atlas are fairly accurate for children and adolescents, although they exhibit ethnic and gender biases. For adult populations, approaches involving bone and skull analysis are more effective, while bone histology methods are suitable for fragmented remains, despite being invasive. Furthermore, the use of artificial intelligence technologies shows significant potential in improving estimation accuracy, although it still requires representative local datasets. This review highlights the importance of adapting methods to the characteristics of the Indonesian population and the need to develop local standards to support a more accurate and equitable forensic identification process.